2021
DOI: 10.1007/s11628-021-00463-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding customer-centric socialization in tourism services

Abstract: Co-creating value with customers has been a strategic focus for tourism companies. Grounded on the organizational socialization theory, this study examines a framework of customer-centric socialization process for tourism providers and how it affects tourists’ co-creation readiness (CCR) and co-creation behavior (CCB) . Through 227 tourists’ responses, the study confirms that tourist education positively influences tourists’ CCB, and CCR part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…But this requires awareness-raising plans. The implementation of tourist-centred socialisation programmes allows for the education of tourists with standardised and personalised tactics to understand their roles towards sustainable models—blue cluster (Yen et al 2021 ). Results encourage to develop new consumption habits to minimise waste management after COVID-19 pandemic—red and green clusters-.…”
Section: Discussionmentioning
confidence: 99%
“…But this requires awareness-raising plans. The implementation of tourist-centred socialisation programmes allows for the education of tourists with standardised and personalised tactics to understand their roles towards sustainable models—blue cluster (Yen et al 2021 ). Results encourage to develop new consumption habits to minimise waste management after COVID-19 pandemic—red and green clusters-.…”
Section: Discussionmentioning
confidence: 99%
“…Second , the review revealed that 123 studies have applied theories to guide their research on VCCB. Table 3 highlights that the majority of the selected studies (53%) used a single theory (Peng et al, 2020; Yen et al, 2021), 36 studies (27%) used a dual combination of theories (Cossío Silva et al, 2013; Wu & Gao, 2019), 10 studies (7%) were based on 3 theories (Chuang & Chen, 2015; Roy et al, 2020), and 5 studies (3%) used integrated multiple theories (Guzel et al, 2020; Tran & Vu, 2021). Third , 13 studies did not rely on any theory to guide their research (e.g., Hussain et al, 2022; Ida, 2017).…”
Section: Tcm Framework‐based Review Of the Studiesmentioning
confidence: 99%
“…The firm may offer a value proposition, but value realization depends on customers’ participation in the service process. Environmental education (Scanlon 2007 ) and co-creation between firms and customers facilitate such participation (Cabiddu et al 2013 ; Lee and Kim 2019 ; Su et al 2016 ; Yen et al 2021 ). Another technique that allows other relevant hotel stakeholders to participate is co-production, which facilitates the integration and application of resources contributed by both suppliers and consumers (Chathoth et al 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%